Potential Applications of Imaging and Image-Guided Radiotherapy for Brain Metastases and Glioblastoma to Improve Patient Quality of Life - Nguyen, Nam P.; Nguyen, Mai L.; Vock, Jacqueline; Lemanski, Claire; Kerr, Christine; Vinh-Hung, Vincent; Chi, Alexander; Khan, Rihan; Woods, William; Altdorfer, Gabor; d'Andrea, Mark; Karlsson, ULF L.; et al. (Frontiers in Oncology, 2013)
Treatment of glioblastoma multiforme (GBM) and brain metastasis remains a challenge because of the poor survival and the potential for brain damage following radiation. Despite concurrent chemotherapy and radiation dose escalation, local recurrence remains the predominant pattern of failure in GBM most likely secondary to repopulation of cancer stem cells. Even though radiotherapy is highly effective for local control of radio-resistant tumors such as melanoma and renal cell cancer, systemic disease progression is the cause of death in most patients with brain metastasis. Preservation of quality of life (QOL) of cancer survivors is the main issue for patients with brain metastasis. Image-guided radiotherapy (IGRT) by virtue of precise radiation dose delivery may reduce treatment time of patients with GBM without excessive toxicity and potentially improve neurocognitive function with preservation of local control in patients with brain metastasis. Future prospective trials for primary brain tumors or brain metastasis should include IGRT to assess its efficacy to improve patient QOL.